Pengembangan Media Puzzle Labirin Digital Pada Mata Pelajaran IPAS Siswa Kelas IV SDN 1 Jenggik Utara - Aria Rizki Ivansyah; Muhammad Sobri; Fitri Puji Astria (Action Research Journal, 2025)
The monotonous learning process causes students to become easily bored and less motivated during learning activities. This condition occurs due to the lack of engaging learning media that can enhance students’ enthusiasm and motivation in the learning process. This study aims to determine the development process, validity, and practicality of digital maze puzzle media in the IPAS subject. The media focuses on the topic “The Uniqueness of the Habits of People Around Me.” In terms of design, the media was developed attractively by presenting images of Sasak cultural elements, including traditional customs, ceremonies, and dances. This research employs a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results of the digital maze puzzle media from the material expert obtained a score of 92% (very valid), from media expert 1 obtained 95% (very valid), and from media expert 2 obtained 93% (very valid). The practicality data were obtained from the teacher’s response, which scored 97% (very practical), and from students’ responses, which scored 93% (very practical). These results indicate that the digital maze puzzle media is highly valid and practical to be utilized as an effective learning medium for fourth-grade students